Sample, sample size and sampling: a review of current recommendations - Gamarra-Moncayo, José (2025)
Introduction: The present review is based on the need to know the current recommendations on the sample, sample size and sampling that are considered in various empirical studies, aspects that certainly can generate confusion especially in novice researchers. In this sense, a theoretical and methodological framework is established that attempts to answer different questions raised on this subject, based on publications in high impact journals, guaranteeing their credibility and suitability. Objective: Provide a guide that offers different views on sample sizes and their practical application for researchers, teachers and students. Method: Theoretical study in the form of a narrative review. Results: Current recommendations revolve around performing power analysis to calculate the sample size, regardless of the type of sampling to be used, in addition to the fact that it is a good practice to be guided by the sample sizes of other studies with similar characteristics, preferably from journals indexed in high-level databases. However, it is necessary to clarify that this work should not be taken as a definitive guide, but that it is the duty of the researcher to be informed of new updates in methodologies that may arise on this subject. Conclusions: The choice of sample size depends on multiple factors that should be carefully analyzed.